Dynamic modelling and intelligent control of a flying machine : part 1 - Poh, Wee Kian (2015)
Unmanned Air Vehicles (UAVs) are commonly used for military purposes. In the recent years, UAVs have gained world-wide interest and the field has been evolving due to the advancements in technology. These advancements thus allow UAVs to be used in commercial industries as well. The objective of this project is to build an intelligent quadcopter with optimal flight performance and high stability. The report covers the research and development of a quadcopter. The design and construction of the quadcopter are also discussed in detail. Modifications are made to the structure of the quadcopter to enhance its capability and flight performance to perform various tasks such as precise payload dropping and flying through a door with plastic chain curtain. This project took part in Singapore Amazing Flying Machine Competition (SAFMC) 2015 and successfully won a Silver Medal in the Semi-Autonomous Category.